Synthesis, characterization and catalytic performance of FeMnTiOx mixed oxides catalyst prepared by a CTAB-assisted process for mid-low temperature NH3-SCR - Wu, Shiguo; Zhang, Lei; Wang, Xiaobo; Zou, Weixin; Cao, Yuan; Sun, Jinfang; Tang, Changjin; Gao, Fei; Deng, Yu; Dong, Lin (Applied catalysis. A, General, 2015)
[Display omitted] •The catalyst expanded operating temperature window and avoided the use of vanadium.•The addition of CTAB increased the ratio of Lewis acid site on the surface of samples.•The addition of CTAB was beneficial for the formation of isolated state active phase.•Anatase crystalline was more conducive to enhance the electron interaction than amorphous TiO2.•NH3 was easier to be activated on the surface of samples which had lower binding energy of lattice oxygen. A series of FeMnTiOx mixed oxides catalysts, which were synthesized by a CTAB-assisted co-precipitation process and calcined at different temperatures, were investigated for selective catalytic reduction of NO with NH3 in the presence of excess O2. The samples were characterized by means of N2-physisorption, XRD, TEM, H2-TPR, XPS, NH3-TPD, and in situ DRIFTS technologies. The results indicated that the activities of samples were not predominately determined by BET specific surface area. Compared with amorphous TiO2, the anatase TiO2 crystalline phase was more conducive to enhance the electron interaction between manganese species and support: Mn4++Ti3+↔Mn3++Ti4+·NH3 was easier to be activated on the surface of samples which had lower binding energy of lattice oxygen in selective catalytic reduction of NO with NH3. The addition of CTAB not only promoted the formation of anatase TiO2 crystalline phase and Lewis acid sites, but also improved the dispersion extent of active phase on the surface of samples. Thus, it enhanced the catalytic performance of samples. In addition, calcination temperature had an important influence on the valence state of manganese species, as well as the dispersion extent of active phase and the crystal phase structure of support. The sample calcined at 400°C showed excellent low-temperature activity and mid-temperature N2 selectivity. The NO conversion and N2 selectivity of this sample were above 90% in the range of 150–350°C at a space velocity of 30,000mLg−1h−1. Furthermore, it exhibited sulfur tolerance and water resistance to a certain extent.